Prevalence of intestinal parasites and the absence of soil-transmitted helminths in Añatuya, Santiago del Estero, Argentina - Periago, Maria Victoria (2018)
Fil: Periago, Maria Victoria. Consejo Nacional de Investigaciones Científica y Técnicas (CONICET); Argentina.